SISTEM INFORMASI PROFIL DAN PENJUALAN BARANG PADA TOKO ADA COMP BERBASIS WEB: Code Igniter;Data Flow Diagram;Hypertext Markup Language;Intype;Services;Media Information;MySQL;PHP;WampServer. - Elzas; Lailyn Puad; Diatmoko, Wahyu (LP2M Universitas Nurdin Hamzah, 2021)
Ada Comp is a place to sell computers and accessories. Since its establishment until now the sales system run by the Ada Comp store is still manual. Buyers must come directly to the store to buy goods and still use the records in the book to find out the specifications of the goods sold, so that making reports requires a lot of time. This is caused because every time there is a change in the stock due to the purchase and sale of goods. From these problems, it is necessary to develop a web-based sales information system that can assist in processing sales well, also helping this shop in managing goods sales to customers more neatly, and avoiding sales errors. The process of making this program begins by analyzing the systems that already exist in the business, then creating DFD and the required tables. Followed by designing the interface and creating the program. This online media uses PHP programming language, MySQL as database, Intype as HTML text editor and for designing websites based on Code Igniter. This application has two main functions. First, for general users, every website visitor can view the product catalog, and order products. Second, the administrator can manage the data of goods, manage orders and obtain reports.